BANK NTB SYARIAH'S SOUNDNESS: A MULTI-METHOD ASSESSMENT USING CAMELS, RGEC, AND ALTMAN Z-SCORE - Syahrir, Dimas Kenn; Hosen, M. Nadratuzzaman; Wahyudi, Ickhsanto (FEB Universitas Sam Ratulangi Manado, 2023)
This paper endeavors to appraise the level of stability of Bank NTB Syariah during the time span of 2019 to 2021, by employing the CAMELS technique (which scrutinizes the bank's Capital, Assets, Management, Earnings, Liquidity, and Market Sensitivity), RGEC (which assesses the Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital), as well as the Altman Z Score method (which analyzes the potential for bankruptcy). The data utilized for this research were procured through the application of documentation techniques and sourced from the financial statements and annual reports of Bank NTB Syariah, from 2019 to 2021. The data analysis technique utilized involved an evaluation of the bank's level of stability, utilizing a risk-based approach, encompassing the CAMELS, RGEC, and Altman Z Score factors. Based on the appraisal of the level of stability of PT. Bank NTB Syariah from 2019 to 2021, as evaluated by the comprehensive RGEC and CAMELS approach, the bank is deemed to be in a sound financial condition. However, the results of the bankruptcy prediction analysis, utilizing the Altman Z Score model, indicate that the financial state of Bank NTB Syariah in 2021 is situated in a nebulous area, albeit superior to its condition in 2020 and 2019, which indicated an indication of financial distress and potential bankruptcy.